2016
DOI: 10.1021/acs.jafc.5b04732
|View full text |Cite
|
Sign up to set email alerts
|

Development of Double Eastern Blotting for Major Licorice Components, Glycyrrhizin and Liquiritin for Chemical Quality Control of Licorice Using anti-Glycyrrhizin and anti-Liquiritin Monoclonal Antibodies

Abstract: Licorice is utilized in various food industries around the world for seasoning agents, confectioneries, drinks, and functional foods. Glycyrrhizin (GL) and liquiritin (Liq) are major quality control chemical markers of licorice that have multifunctional bioactivities. Chemical quality control of licorice is important because its component profiles change depending environmental factors (climate, soil condition, and water deficit) and differences between species. Double eastern blotting using anti-GL and anti-L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The establishment of a double EB by immunostaining using anti-GA and anti-liquiritin (Liq) MAbs was successfully applied in determining the immunohistochemical distribution and localization of GA and Liq in fresh licorice root. Moreover, its application to identify GA and Liq in licorice and Kampo medicines was also reported [ 87 ].…”
Section: Immunoassay For Mpnp Using Mabsmentioning
confidence: 99%
“…The establishment of a double EB by immunostaining using anti-GA and anti-liquiritin (Liq) MAbs was successfully applied in determining the immunohistochemical distribution and localization of GA and Liq in fresh licorice root. Moreover, its application to identify GA and Liq in licorice and Kampo medicines was also reported [ 87 ].…”
Section: Immunoassay For Mpnp Using Mabsmentioning
confidence: 99%
“…Quality control of licorice root is needed to assure uniformity in the concentrations of these compounds, which can differ according to licorice species, growth place, and harvest season, and so on. To this end, we previously prepared MAbs against GC [4] and Liq [16] and developed an eastern blotting system for detection of GC and Liq and their aglycones (glycyrrhetinic acid and liquiritigenin, respectively) [17] in order to make evident the resource of licorice for further researches. In this method, crude licorice extract and/or traditional Chinese medicine extract are developed on a Thin acrosome reaction in sperm.…”
Section: Components Of Licorice and Quantitative And Qualitative Controlmentioning
confidence: 99%
“…Modern research studies showed that GRER had extensive pharmacological effects in antispasmodic, antidiabetic, antiosteoporosis, antidepressive, antitussive and expectorant, hepatoprotective, and memory-enhancing [5][6][7][8][9][10][11]. e major bioactive components of GRER were saponins, flavonoid glycosides, and free phenolic compounds [12]. Approximately 250 compounds have been reported from GRER, and more than 151 compounds in GRER have been determined up to present [13].…”
Section: Introductionmentioning
confidence: 99%